2021
DOI: 10.1042/bcj20210295
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of self-assembly and target binding in centrin 1 from Toxoplasma gondii

Abstract: Centrins are conserved calcium (Ca2+)-binding proteins typically associated with centrosomes that have been implicated in several biological processes. In Toxoplasma gondii, a parasite that causes toxoplasmosis, three centrin isoforms have been recognized. We have recently characterized the metal binding and structural features of isoform 1 (TgCEN1), demonstrating that it possesses properties consistent with a role as a Ca2+ sensor and displays a Ca2+-dependent tendency to self-assemble. Herein, we expanded ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…Studies on centrins have suggested that Ca 2+ -induced polymerization appears to depend on this amino-terminal domain [60]. In both HsCEN2 and TgCEN1, this N-terminal extension is needed for self-assembly induced by Ca 2+ [60][61][62][63]. [48][49][50]62] Homo sapiens HsCEN3 O15182 3…”
Section: Centrins Have Large Differences In Their Ability To Sense Ca 2+mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on centrins have suggested that Ca 2+ -induced polymerization appears to depend on this amino-terminal domain [60]. In both HsCEN2 and TgCEN1, this N-terminal extension is needed for self-assembly induced by Ca 2+ [60][61][62][63]. [48][49][50]62] Homo sapiens HsCEN3 O15182 3…”
Section: Centrins Have Large Differences In Their Ability To Sense Ca 2+mentioning
confidence: 99%
“…Thus, HsCEN2 and CDC31 have the ability to bind targets in their C-terminal via a hydrophobic pocket, even independently of Ca 2+ [19,21,49,52,64,69,76]. Notwithstanding, for some centrins, target binding through the N-terminal domain has also been documented [52,63].…”
Section: Functional Diversity and Specialization Of Centrinsmentioning
confidence: 99%
“…Structural studies of centrin interactions have revealed that the basis for the target selectivity of centrins lies in their ability to interact with regions that have the propensity to form an α-helix and contain a hydrophobic triad, namely W 1 xxL 4 xxxL 8 (1–4–8 motif), which can be either in a forward (W 1 L 4 L 8 ) or reverse (L 8 L 4 W 1 ) orientation [ 6 , 12 , 18 ]. This sequence has been found in many centrin–target complex structures and validated by various biophysical techniques [ 6 , 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 77%
“…The recombinant TgCEN1 (lacking the first 21 residues) and its N-terminal (N-TgCEN1, 22–94 aa) and C-terminal (C-TgCEN1, 95–169 aa) domains were purified as previously described [ 19 , 31 ]. The TgSFI1 peptides were synthesized by GenScript U.S.A. Inc. (Piscataway, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation